Incorporating Blended Learning into ESL Writing Classrooms: Issues and Challenges - Othman, Noor Ahnis; Rahmat, Noor Hanim; Ahmad, Fathiyah; Bahasa, Akademi Pengajian (American Journal of Social Sciences and Humanities, 2019)
This paper presents the issues and challenges faced by the learners when blended learning is being incorporated into ESL writing classrooms. Blended learning makes use of features from the traditional classroom which are further incorporated into lessons with the help of technology.It combines independent learning with valuable face-to-face interaction with a facilitator. This study highlights on 39 students from different semesters who attended the academic writing course in a public university in Malaysia. The instrument used is a survey containing 4 sections; demographic profile, learners’ reasons, perceived difficulties in writing and learners’ perception on blended learning in general. The findings from this study revealed that teachers with low proficiency and lack in knowledge demotivate the learners during their writing lessons. The non-careful use of punctuations has impeded the learners writing. The implication of this study is that blended learning can be incorporated into ESL writing classes as long as teachers are trained and knowledgeable to use technology in their lessons.